2014
DOI: 10.22226/2410-3535-2014-2-89-92
|View full text |Cite
|
Sign up to set email alerts
|

Features of deformation and breaking for Ni nanowire

Abstract: Molecular dynamics (MD) simulations have been carried out on pure Nickel (Ni) crystal with face-centered cubic (FCC) lattice upon application of uniaxial tension at nanolevel with a speed of 20 m / s. The deformation corresponds to the direction <001>. To the calculated block of crystal free boundary conditions are applied in the directions <100>, <010>. A manybody interatomic potential for Ni within the second-moment approximation of the tight-binding model (the Cleri and Rosato potentials) was employed to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Aish et al [5][6][7] have studied the mechanical properties of Ni nanowires using pair potential Morse where they concluded that the mechanical properties of Ni nanowires are highly dependent on the size, shape as well as the atomic vacancies in the nanowire.…”
Section: Molecular Dynamic Potentialmentioning
confidence: 99%
“…Aish et al [5][6][7] have studied the mechanical properties of Ni nanowires using pair potential Morse where they concluded that the mechanical properties of Ni nanowires are highly dependent on the size, shape as well as the atomic vacancies in the nanowire.…”
Section: Molecular Dynamic Potentialmentioning
confidence: 99%
“…The following sections discuss MD simulation methodology, properties of FCC nanowires, and comparison of their properties with body-centered cubic (BCC) and hexagonal closed-packed (HCP) nanowires. The mechanical properties of Ni nanowires dependence on size, shape, as well as the temperature have been studied [1][2][3][4][5][6][7]. Characterization of strain-induced structural transformations in CdSe nanowires using molecular dynamics simulation also studied [8].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of such properties of some nanostructures is still unclear. Aish et al [3][4][5][6][7] have showed that the mechanical properties of Ni nanowires are highly dependent on the size, shape as well as the atomic vacancies in the nanowire.…”
Section: Introductionmentioning
confidence: 99%